Cidade, meio ambiente e lixo urbano: evolução da gestão dos resíduos sólidos em Belo Horizonte - Ribeiro, José Perpétuo Caldeira (2010)
This research is a debate about solid residues management, as modeled and standardized by Belo Horizonte´s Executive Office, whose goal of attending the environmental regulations, promoting sustainability and the administration of socioenvironmental conflicts in the urban area, thus fulfilling its social function. This research will analyze the evolution of municipal Urban Cleaning management and its present status, trying to assert the viability and adequacy of the chosen paths and actions pursued by the present municipal administration. It approaches the serious urban problem that garbage represents, especially, when one considers the increasing consumption and disposal; the garbage in the public pathways, obstructing mouth-of-wolf and galleries; the garbage dumps, focus of attraction of vectors and, of animals and scavengers; the undignified situation of needed people, oblivious to scavenging risks; the contamination of soil, water and air; amongst others. The city of Belo Horizonte was adopted as the object of analysis. We have analyzed public documents from the city hall, the state and the federation besides politic, historical, social, economic, environmental and technical texts. Interviews were made with public employees of the Urban Cleaning Superintendence of Belo Horizonte SLU; the Municipal Secretary of Environment SMMA; the State Environmental Foundation FEAM; the Center for Treatment of Solid Residues at BR-040 CTRS BR-040 and the Agency for the Metropolitan Region of Belo Horizonte Agency RMBH. Two other interviews had been granted by the presidents of two Associations of Inhabitants of districts surrounding the landfill and a third, given by a Hoje em Dia newspaper editor. Public documents were consulted at Abílio Barreto Historical Museum MHAB, Mineiro Public Archive APM, and the Public Archive of the City of Belo Horizonte APCBH. The management of the solid residues in Belo Horizonte is in the right way, studying and adopting advanced actions and instruments, based on the 3 Rs, on social participation and on the solidary economy. Finally, the great jump was planted and is germinating: the inter-municipal shared public management